Debt Collector Ethics in Comparative Perspective Toward Balancing Creditor Interests and Consumer Protection: (Case Study of Kotamobagu District Court Decision Number 97/Pdt.G.S/2022/PN Ktg) - Hayatuddin, Raihan Ramadhan; Putri, Citraresmi Widoretno (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
Debt collection practices by third-party collectors generate persistent tension between the contractual rights of financing institutions and the legally protected entitlements of consumers. This study examines how debt collection ethics can be structured to simultaneously serve creditor interests and safeguard consumer rights, employing a normative juridical methodology with comparative and case-based approaches across four jurisdictions: Indonesia, the United States, the United Kingdom, and Australia. Analysis of the Kotamobagu District Court Decision Number 97/Pdt.G.S/2022/PN Ktg reveals that violations of collection ethics impose direct legal liability on financing institutions. The comparative analysis demonstrates that Indonesia's regulatory framework remains fragmented and lacks enforcement coherence, in contrast to the dedicated federal statute of the United States, the United Kingdom's mandatory licensing regime, and Australia's substantial financial penalties. This study concludes that equilibrium between creditor and debtor interests is achievable only through five core ethical principles: transparent communication, proportionality of enforcement, strict adherence to fiduciary execution procedures, respect for fundamental consumer rights, and full institutional accountability for collector conduct. These findings underscore the urgency of enacting a comprehensive, standalone regulatory instrument governing debt collection in Indonesia.